2002
DOI: 10.1017/s002185370100809x
|View full text |Cite
|
Sign up to set email alerts
|

Madheruka and Shangwe: Ethnic Identities and the Culture of Modernity in Gokwe, Northwestern Zimbabwe, 1963–79

Abstract: In colonial Southern Rhodesia, administrative officials often couched the rhetoric of ‘modernization’ in ethnic terms. They regarded immigrant Madheruka master farmers as the embodiment of modernization because they had been exposed to forces of modernization in their areas of origin, while both officials and immigrants alike regarded indigenous Shangwe as backward and primitive. This article argues that the construction of Madheruka and Shangwe ethnic identities dates primarily to the early 1960s, with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Origins of the term Shangwe are not clear, but there were several versions given in different oral accounts. Nyambara (2002) gives the impression that the term Shangwe began to be used by immigrants from the south in the 1960s to refer to indigenous people they found in the north of Zimbabwe. He also gives evidence showing that these people began to be referred to as Shangwe people in pre-colonial times.…”
Section: Migration Of the Batonga And Shangwe Into The Zambezi Valleymentioning
confidence: 99%
See 2 more Smart Citations
“…Origins of the term Shangwe are not clear, but there were several versions given in different oral accounts. Nyambara (2002) gives the impression that the term Shangwe began to be used by immigrants from the south in the 1960s to refer to indigenous people they found in the north of Zimbabwe. He also gives evidence showing that these people began to be referred to as Shangwe people in pre-colonial times.…”
Section: Migration Of the Batonga And Shangwe Into The Zambezi Valleymentioning
confidence: 99%
“…To indigenous people of Gokwe, the term Shangwe describes frequent droughts and famines that often devastated that area in the pre-colonial period. Gokwe is generally a very dry area and prone to periodic drought and famine (Nyambara, 2002). Therefore, landscape qualities and features were used to cast derogatory identities by dominant ethnic groups upon seemingly weak ones.…”
Section: Migration Of the Batonga And Shangwe Into The Zambezi Valleymentioning
confidence: 99%
See 1 more Smart Citation
“…This focus on settler-African conflicts over land reflects the centrality of land in anticolonial struggles in Zimbabwe, but it has also discouraged an examination of conflicts over land among both settlers and Africans. However, as a number of relatively recent studies has shown, exclusions along lines of ethnicity and gender existed among Africans in colonial and postcolonial Zimbabwe (Dzingirayi, 1994;Nyambara, 1999Nyambara, , 2002 and were exacerbated by colonial and postcolonial state intrusions in African agrarian lives (Alexander, 2006;Moore, 2005). Although these recent studies (e.g., Nyambara, 1999Nyambara, , 2002 have paid attention to gender and ethnicity in the politics of land, Stoler's (1992: 320) observation that in the former colonial world, ''the objects of .…”
Section: Introductionmentioning
confidence: 99%
“…In so doing, the study builds on a growing body of scholarship examining the intersection of forced resettlement and identity formation in Zimbabwe. Examples of such literature include Worby’s (1994) and Nyambara’s (2002) studies of developments that took place in Gokwe district after the resettlement of evictees from Rhodesdale Ranching Estates near the town of Kwekwe. With slight differences of emphasis, both scholars concluded that ethnic labeling and counterlabeling became a daily occurrence in that area.…”
Section: Introductionmentioning
confidence: 99%